Płeć a realizacja praw wyborczych - Urbaniak, Krzysztof (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Women’s voting rights and exercise thereof are the subjects of a dispute unfolding on normative, cultural, ideological, and emotional levels. For a considerable period of time said dispute concerned granting women full suffrage, which was perceived as an element of the realization of a general rule of equality. Since the second part of the twentieth century, we have been witnessing yet another chapter in the dispute surrounding women’s suffrage concerning the introduction of mechanisms promoting women in the election process both inside political parties and in the normative sphere, using such instruments as electoral gender quotas, parity, and the so-called „zipper rule” for electoral lists. This article analyzes the issue of women’s suffrage, including gender census and political and legal conditions for introducing reverse discrimination, used to increase the representation of women on electoral lists. The author attempts to answer the question of whether gender is a relevant factor in exercising voting rights and to what degree the realization of the constitutional principle of equality is compatible with introducing into the legal system instruments whose aim is to strengthen the representation of women in representative bodies
Keywords: prawa wyborcze; kobiety; cenzus płci; zasada równości; kwoty i parytety